Modeling Multi-Cascade Fuzzy Controller with Integrated Implementation of Various Control Laws - Buzikayeva, Alina V.; Susdorf, Viktor I.; Cherniy, Sergey P. (2019 International Ural Conference on Electrical Power Engineering (UralCon), 2019)
The paper presents the DC drive control system, on the basis of which the model of multi-cascade fuzzy control system is developed. The analysis of the existing approaches to construction of fuzzy control systems is performed. An intelligent control system with shared position and speed control is developed and implemented. A comparative study of control systems constructed using the classic and fuzzy approaches is conducted. The introduction of such technology of multi-stage fuzzy systems with the implementation of a single intelligent control module for complex electric drive systems will allow implementing a control system for a whole class of electric drive systems, taking into account the incompleteness and inconsistency of the source data, as well as all the features and relationships between coordinates in a complex control object. The combination of different fuzzy logic inference algorithms allows solving the tasks of intelligent control for multi-objective and multi-factor tasks.